Dynamics of Gono-Gini Property in Marriage: A Comparative Analysis of Indonesian Civil Law, Islamic Family Law, and Javanese Customary Law - Khoirul Dwi Safe’i; Ghozel Indrawan; Hamdan Arifin; Nike Ade Anggaeni; Abid Assidiqi Zahra; Fayyad Akram; Annikmah Farida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The concept of harta gono-gini (joint marital property) constitutes a fundamental pillar of Indonesian family law, reflecting principles of economic justice and shared responsibility between spouses. This study aims to comparatively analyze the regulation and implementation of joint property within three major legal systems operating in Indonesia, namely Indonesian Civil Law, Islamic Family Law, and Javanese Customary Law. Using a normative legal research method supported by limited empirical data, this research examines statutory provisions, legal doctrines, court decisions, and living customary norms related to marital property.The findings reveal that all three legal systems substantively recognize joint property as assets acquired during marriage through the mutual contribution of husband and wife. However, significant differences emerge in their philosophical foundations and mechanisms of distribution. Indonesian Civil Law emphasizes formal legal certainty and tends to apply an equal division principle, while Islamic Family Law prioritizes proportional justice based on both economic and non-economic contributions. Meanwhile, Javanese Customary Law focuses on social harmony, moral values, and contextual fairness, often resolving disputes through family deliberation rather than formal litigation.The coexistence of these legal systems illustrates Indonesia’s legal pluralism, which creates both opportunities for contextual justice and challenges in the form of legal disharmony and jurisdictional overlap. This study concludes that legal pluralism in joint property regulation should be viewed as a legal asset rather than an obstacle. Therefore, an integrative approach to harmonizing national family law is necessary to ensure legal certainty while accommodating substantive justice aligned with Indonesia’s socio-cultural diversity.